Crystal structure, hirshfeld analysis and DFT study of 6,7-dimethoxy-3-[(5-chloro-1,3,3-trimethylindolin-2-ylidene)methyl]isobenzofuran-1(3h)-one - Suhaila Sapari,; Emma Izzati Zakariah,; Noraisyah Abdul Kadir Jilani,; Sheryn Wong,; Mohammad Fadzlee Ngatiman,; Siti Aishah Hasbullah, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The coupling reaction of 5-chloro-1,3,3-methylenindoline with 6-formyl-2,3-dimethoxy benzoic acid under solvent-free microwave irradiation gave of 6,7-dimethoxy-3-[(5-chloro-1,3,3-trimethylindolin-2-ylidene)methyl]isobenzofuran- 1(3H)-one, C22H22ClNO4 in high yield. The molecular structure consists of indoline system (C1-C8/N1) and isobenzofuran system (C10-C17/O1) connected by the enamine carbon. The title compound is crystallised in P21/n space group, Z’=4 with two independent molecules in centrosymmetric dimer. By using Hirshfeld surface and two-dimensional fingerprint plots, the presence of short intermolecular interactions and π-π stacking in the crystal structure were analysed. The DFT study is performed by comparing the calculation data with the X-ray data and analysing the HOMO and LUMO value, which gave -0.26952 a.u. and -0.17760 a.u., respectively.